What If It Was You (#WIIWY) digital activism on TikTok to fight gender-based violence online and cyberbullying - Fatimatuzzahro Fatimatuzzahro; Zainal Abidin Achmad (Masyarakat, Kebudayaan dan Politik, 2022)
FISIP 21 created #WIIWY activism in response to the increase in cases of online gender-based violence (KBGO) and cyberbullying during the COVID-19 pandemic. To be able to participate in activism, the public can upload content on the social media TikTok. The #WIIWY movement is gaining traction among the general public. This study explored the motivations of #WIIWY digital activism makers, obtained information about the dissemination of #WIIWY digital activism on TikTok, and the role of TikTok in the process of making digital activism media. This study uses a virtual ethnographic method to explain the cultural behavior of digital activism that is used by users on TikTok. The results of this study indicate that there are several individual motivations involved in #WIIWY activism, namely the suitability with feelings, want to spread awareness about cyberbullying and KBGO, voice the experiences as victims of crime on social media and create a safer and more positive social media environment. The spread of this activism is quite high but its virality is limited at the beginning and is not evenly distributed throughout Indonesia. This study concludes that TikTok plays a role in the media-making process of producing and disseminating #WIIWY activism.